The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/bjet.13009
|View full text |Cite
|
Sign up to set email alerts
|

Reasons associated with preservice teachers’ intention to use immersive virtual reality in education

Abstract: His work spans the fields of learning design, teacher education, technology-enhanced learning and computing education. He is intensely curious about how emerging technologies may be used to enhance learning outcomes and experiences. Dorothy DeWitt is an associate professor in the Department of Curriculum and Instructional Technology at the Faculty of Education, University of Malaya. Her interests are in designing learning environments for problem-solving and collaboration, mobile learning and knowledge buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 48 publications
5
60
1
2
Order By: Relevance
“…In other words, increasing the enjoyment of using mobile apps for science teaching and the degree of focus on the effectiveness of using mobile apps strengthens teachers' attitudes, which in turn strengthens their intention to use mobile apps in science teaching. These results are consistent with some studies that identified the prominent role of the perceived enjoyment and concentration in explaining teachers’ technology acceptance in education (Bower et al, 2020 ; Hu et al, 2020 ). Therefore, the study made important contributions to the literature by revealing the importance of these crucial constructs’ relationships within the context of using mobile applications in science teaching.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, increasing the enjoyment of using mobile apps for science teaching and the degree of focus on the effectiveness of using mobile apps strengthens teachers' attitudes, which in turn strengthens their intention to use mobile apps in science teaching. These results are consistent with some studies that identified the prominent role of the perceived enjoyment and concentration in explaining teachers’ technology acceptance in education (Bower et al, 2020 ; Hu et al, 2020 ). Therefore, the study made important contributions to the literature by revealing the importance of these crucial constructs’ relationships within the context of using mobile applications in science teaching.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, perceived control is defined as the level of an individual’s control over the environment and the individual’s actions (Koufaris, 2002 ). The study by Bower et al ( 2020 ) and Hu et al (Hu et al, 2020 ) state that perceived enjoyment is a key motivator for influencing teachers’ attitude toward the use technology and, ultimately, teachers’ intentions to use it. Similarly, perceived control is described as one of the constructs that most influences teachers’ intentions to use technology (Somchai & Damnoen, 2020 ; Teo et al, 2016 ).…”
Section: Literature Review and Study Hypothesesmentioning
confidence: 99%
“…Hedonistic advantages of the technology likely play a more important role in private contexts than, e.g., its usefulness. However, the hedonistic motivation was rated highest by prospective preservice teachers compared to all other aspects in the study of Bower et al [32]. Herz and Rauschnabel [33] focused their research in the consumer context on the technology-specific aspects of wearability, immersion, and user concerns.…”
Section: 2mentioning
confidence: 99%
“…Even if UTAU2 was developed in 2012, it is still a fashionable framework in a large variety of fields, like Internet of Things (IoT) (Alkawsi et al , 2020), autonomous vehicles, m-banking (Lin et al , 2020) but also virtual reality (VR) in education (Bower et al , 2020), e-learning (Almaiah and Alyoussef, 2019) or m-learning (Kumar et al , 2020). Each domain we mention before has particularities, and the generic UTAUT2 requires customization in accordance.…”
Section: Introductionmentioning
confidence: 99%